$\mathcal{H}$-Stability of Runge-Kutta Methods with Variable Stepsize for System of Pantograph Equations (Journal of Computational Mathematics, 2004)
This paper deals with $\mathcal{H}$-stability of Runge-Kutta methods with variable stepsize for the system of pantograph equations. It is shown that both Runge-Kutta methods with nonsingular matrix coefficient $A$ and stiffly accurate Runge-Kutta methods are $\mathcal{H}$-stable if and only if the modulus of stability function at infinity is less than 1.